Institutional And Governance Complexity Of Payangan Marine Jember Tourism - M. Hamdi HS; Itok Wicaksono; Gusti Made Darma (POLITICO, 2023)
High enthusiasm for marine tourism has driven the development of this sector in many places, but suboptimal management, as in Payangan and Jember, is actually discouraging visitors from returning. The cause of this reluctance is suspected to be due to suboptimal governance and institutional management. This study uses Soft Systems Methodology (SSM) to analyze these complexities in six stages. The findings show that there are 24 problems in governance and institutions in Payangan, including a lack of formal regulation enforcement and barriers to local community participation. Management groups tend to prioritize economic gains over the overall well-being of the community. Based on the results of this study, it is concluded that consensus is needed in enforcing regulations (formal constraints) and community participatory activities (informal constraints) to achieve sustainable governance. The proposed conceptual model integrates governance and institutional concepts to strengthen regulation and participation, with a focus on collaboration between management groups and local communities. Comparison between the conceptual model and the field situation shows the need for systematic change implementation that considers the interests of all stakeholders. Thus, this study offers an SSM-based strategy to improve the effectiveness of governance and institutions in marine tourism management, especially in Payangan and Jember, by strengthening regulation and increasing community participation. These steps are expected to provide a stronger foundation for the sustainable development of the marine tourism sector in the future.